AB0984 Detailed Analysis of MRI Lesions in Subjects with ACPA but NO Clinical Signs of Arthritis. (10th June 2014) - Kleyer, A.; Krieter, M.; Faustini, F.; Kämmerer, N.; Rech, J.; Schett, G.
Abstract : Background: Autoimmunity develops long before the development of clinically signs of inflammation in patients with rheumatoid arthritis (RA). In this context the appearance of autoantibodies against citrullinated proteins (ACPA) may be an important step promoting the transition from autoimmunity to inflammatory disease. Objectives: We hypothesized that healthy ACPA-positive individuals with no clinical signs of arthritis show subclinical soft tissue inflammation in their joints, which can be detected by magnetic resonance imaging (MRI). Methods: Twelve ACPA positive healthy individuals without clinical signs of arthritis and normal acute phase reactant levels received an MRI (Siemens 1, 5 Tesla Aera) examination of the dominant hand. Patients were taken from a cohort of ACPA-positive healthy individuals established at the University of Erlangen-Nuremberg. T1- and T2-weigthed MRI sequences were scored for synovitis, osteitis and bone erosions according to the OMERACT rheumatoid arthritis MRI scoring system (RAMRIS) by two independent assessors. Furthermore, the presence or absence of tenosynovitis was recorded. Results: Data of twelve ACPA positive individuals [10 females (average age 49, 8), 2 males (age: 54/39)] were analyzed. Mean level of CCP-antibodies were 251, 7 U/ml (cut off: 10 U/ml), mean level for MCV–antibodies were 335 U/ml (cut off: 20 U/ml). Six subjects were also positive for rheumatoid factor (RF) with a mean level of 65, 9 IE/ml (cut off 20 IE/ml). Synovitis (not higher than grade 1 in OMERACT Score) was seen in 7/12 subjects affecting 13% (11/84) of all assessed joints. Due to low-grade synovitis inter-reader reliability was low (κ-coefficient 0, 53). Osteitis was detected in 3/12 subjects, involving 2, 1% (6/276) of the evaluated bones. Osteitis was exclusively found in the carpal bones when present. Inter-reader reliability was high (κ-coefficient 1, 00). Tenosynovitis of the extensor and/or flexor tendons was rather frequent and found in 7/12 subjects. Small bone erosions were seen in 9/12 subjects affecting 5, 8% (16/276) of the bone surface. 75% of erosions did affect the carpal bones. Conclusions: A subset of healthy ACPA-positive individuals, which are at risk for developing RA, show distinct inflammatory lesions in the MRI. The carpal joints are the preferentially affected anatomical region, whereas the MCP joints are rarely and the PIP joints never affected. Tenosynovitis was frequently present support the concept that inflammatory lesions in RA start in the tendons around the wrist. Acknowledgements: * AK and MK contributed equally to this work Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3437